Risk factors for asphyxia neonatorum in full-term newborns at the University Hospital of Mahajanga Madagascar - Razanamanana, Safidisoa N.; Henintsoa N. Raveloharimino; Setra H. Rambeloson; Norotiana H. Rabesandratana; Diavolana K. Andrianarimanana (International Journal of Contemporary Pediatrics, 2023)
Background: The aim of this survey was to study the risk factors associated with asphyxia neonatorum in full-term newborns in the neonatal unit in Child and Mother Complex at Androva Mahajanga Hospital. Methods: This was a retrospective case-control study conducted from August 2016 through September 2018. Results: The prevalence of neonatal asphyxia was 5.9%. Determinant factors for birth asphyxia were maternal education level below the tenth grade [OR=1.8 (1.2-2.6), p=0.003] especially if the mother was illiterate [OR=2.3 (1.5-3.6), p<0.001]; less than four prenatal care check-ups [OR=2.9 (1.7-4.9), p<0.001]; presence of maternal disease during pregnancy [OR=2.4 (1.6-3.6), p<0.001], arterial hypertension [OR=3.4 (1.6-7.2), p<0.001]; duration of labour ≥24h [OR=2.1 (1.2-3.6); p=0.007] ; rupture of membranes ≥12h [OR=2.9 (1.6-5.3), p<0.001]; labour outside teaching hospital [OR=21,1 (8,9-49,5), p<0,001]; home birth [OR=26.7 (3.6-199), p<0.001]. Conclusions: Good monitoring of pregnancy, training of providers in neonatal resuscitation, and an increase in technical platforms could reduce the incidence of perinatal asphyxia.